The value of CD47 and CAP1 levels in early diagnosis and MACE prediction for patients with non-ST-segment elevation myocardial infarction - Mingyang Li; Dongxia Jin; Cun Xie; Xiaodong Cui; Hongliang Cong; Yuecheng Hu (BMC Cardiovascular Disorders)
Abstract Background Cardiovascular diseases, particularly atherosclerosis, remain a leading cause of global mortality, presenting significant challenges with non-ST-segment elevation myocardial infarction (NSTEMI). Novel biomarkers such as cluster of differentiation 47 (CD47) and adenylate cyclase-associated protein 1(CAP1) have emerged as potential candidates for improving early diagnosis and risk stratification in NSTEMI patients. Methods This prospective cohort study was conducted at Tianjin Chest Hospital from November 2023 to June 2024, involving a total of 270 patients categorized into NSTEMI and unstable angina (UA) groups. We used multivariable logistic regression analysis to elucidate the relationship between CD47, CAP1, and the onset of NSTEMI. Receiver operating characteristic (ROC) curve analysis was used to evaluate the diagnostic value of CD47 and CAP1 as biomarkers for the early diagnosis of NSTEMI in the population.Subsequently, Cox regression models were utilized to conduct short-term (median follow-up of 146 days) assessments of patients, evaluating the role of CD47 and CAP1 in early risk stratification. Results In our study, CD47 and CAP1 exhibited strong correlations with NSTEMI patients. Furthermore, in ROC analysis, CAP1 (AUC = 0.827, 95% CI: 0.778–0.875, P<0.001) and CD47 (AUC = 0.807, 95% CI: 0.756–0.859, P<0.001) demonstrated robust diagnostic value. Cox regression analysis identified CD47 (HR, 1.059; 95% CI 1.010–1.110; P = 0.018) and CAP1(HR, 5.385; 95% CI 1.769–16.388; P = 0.003) as independent predictors of short-term major adverse cardiovascular events (MACE) in NSTEMI patients. After adjusting some variables, high CD47 group (HR: 4.017, 95%CI 1.320−12.224, P = 0.014) and high CAP1 group (HR: 3.893, 95% CI 1.366–11.090, P = 0.011) the risk of developing MACE was significantly increased in the lower group. Conclusion CD47 and CAP1 demonstrated robust diagnostic value for early NSTEMI and great predictive power for short-term MACE in NSTEMI patients.